Managerial Role In Implementing The Duties And Functions Of The Regional Secretary Of Pasaman Regency (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2022)
According to Law No. 23 of 2014, the duties and obligations of the regional secretary are to assist the heads in formulating policies and coordinating the implementation and administrative services of the apparatus. The managerial problems are the regent's policies outside the annual activity plan of the district, coordination between heads, and determination of the Regional Apparatus Organization (RAO) head. Therefore, this study aims to determine the managerial role in carrying out the duties and functions of the Regional Secretary in Pasaman Regency using qualitative method. It also uses purposive sampling technique for data sources with certain considerations. The primary data sources used are field observations and interviews with all elements related to the research problem. Meanwhile, the secondary data were obtained from library documents from the Pasaman Regency Government. This study divided the four basic management functions according to George R. Terry and processed analyzers and creators for Planning, facilitators and navigators for Organizing, mentors, coordinators for Actuating, and auditors and evaluators for Controlling. The results show that the problems faced by the local government can be solved by the managerial role in planning activities, managing the organization, organizing and supervising activities. The regional secretary can carry out the role of the analyzer, creator, facilitator, navigator, mentor, coordinator, auditor, and evaluator in conducting the main duties, powers, and functions.